Interspecies killing activity of Pseudomonas syringae tailocins. Issue 11 (7th November 2022) - Weaver, Savannah L.; Zhu, Libin; Ravishankar, Sadhana; Clark, Meara; Baltrus, David A.
Abstract : Tailocins are ribosomally synthesized bacteriocins, encoded by bacterial genomes, but originally derived from bacteriophage tails. As with both bacteriocins and phage, tailocins are largely thought to be species-specific with killing activity often assumed to be directed against closely related strains. Previous investigations into interactions between tailocin host range and sensitivity across phylogenetically diverse isolates of the phytopathogen Pseudomonas syringae have demonstrated that many strains possess intraspecific tailocin activity and that this activity is highly precise and specific against subsets of strains. However, here we demonstrate that at least one strain of P. syringae, USA011R, defies both expectations and current overarching dogma because tailocins from this strain possess broad killing activity against other agriculturally significant phytopathogens such as Erwinia amylovora and Xanthomonas perforans as well as against the clinical human pathogen Salmonella enterica serovar Choleraesui s . Moreover, we show that the full spectrum of this interspecific killing activity is not conserved across closely related strains with data suggesting that even if tailocins can target different species, they do so with different efficiencies. Our results reported herein highlight the potential for and phenotypic divergence of interspecific killing activity of P. syringae tailocins and establish a platform for further investigations into the evolution of tailocin host range and strain specificity.